Separation of Anti‐Phase Signals Due to Parahydrogen Induced Polarization via 2D Nutation NMR Spectroscopy. Issue 5 (23rd January 2017) - Obenaus, Utz; Althoff‐Ospelt, Gerhard; Lang, Swen; Himmelmann, Robin; Hunger, Michael
Abstract: The present work introduces a novel method for the selective detection of 1 H NMR anti ‐phase signals caused by the pairwise incorporation of parahydrogen into olefins on noble‐metal‐containing catalysts. Via a two‐dimensional (2D) nutation NMR experiment, the anti ‐phase signals of hyperpolarized 1 H nuclei are separated due to their double nutation frequency compared to that of thermally polarized 1 H nuclei. For demonstrating this approach, parahydrogen induced polarization (PHIP) was achieved via the hydrogenation of propene with parahydrogen on platinum‐containing silica and investigated by in situ 1 H MAS NMR spectroscopy under continuous‐flow conditions, that is, the hydrogenation reaction was performed inside the magnet of the NMR spectrometer. The 2D nutation NMR experiment described in the present work is useful for the separation of overlapping anti ‐phase and in ‐phase signals due to hyperpolarized and thermally polarized 1 H nuclei, respectively, which is important for research in the field of heterogeneous catalysis. Abstract : Hydrogenation : Two‐dimensional nutation NMR experiments are demonstrated to be suitable for separating anti ‐phase 1 H NMR signals caused by parahydrogen induced polarization (PHIP). The pairwise incorporation of parahydrogen into propene is investigated on platinum‐containing silica using in situ 1 H MAS NMR spectroscopy under continuous‐flow conditions.